The Influence of Leadership in Audit Teams on Audit Effectiveness - Noch, Muhammad Yamin (Manunggal Halim Jaya, 2024)
The research investigates the influence of leadership within audit teams on audit effectiveness, aiming to understand the dynamics between leadership styles and contextual factors in shaping audit outcomes. Employing a quantitative descriptive approach, data is collected through surveys administered to audit professionals across various industries. Leadership styles, including transformational, transactional, and laissez-faire approaches, are assessed alongside contextual factors such as organizational culture, audit complexity, and team composition. Results reveal that transformational leadership positively correlates with audit quality and team performance, while transactional and laissez-faire leadership exhibit varying effects. Organizational culture, particularly ethical leadership practices, significantly influences audit effectiveness, fostering trust, accountability, and adherence to professional standards. Audit complexity moderates the relationship between leadership and audit effectiveness, highlighting the importance of adaptability and strategic acumen in guiding audit teams through complex engagements. Moreover, team composition, specifically diversity, impacts leadership dynamics and team performance, emphasizing the need for inclusive leadership practices. Overall, the study contributes to a nuanced understanding of the role of leadership in audit effectiveness, providing insights for audit firms and organizations to optimize leadership practices and enhance audit outcomes.